Agriculture Export Supply Chain Management in Belgorod Region - Kolesnikov, A.V; Nasedkina, T.I; Zdorovets, Yu.I; Chernykh, A.I; Gruzdova, L.N (International Journal of Supply Chain Management, 2020)
Abstract- The export potential of a country determines the development of its economy, profit-making organizations, and a high level of competitiveness in the world markets of goods. Supply chain management can be utilized in export system to improve the efficiency and make it easy for the receiver and sender. So, in this paper impact of the supply chain management in agricultural potential for export investigated. In addition, a high share of exports characterizes the internal supply of goods, the ability to produce it at lower costs than competitors. The strategic direction in this direction is the export of food. As you know, Russia has reached the indicators of the Food Security Doctrine, and now it is possible to export agricultural products. One of the developed agricultural regions of Russia is Belgorod region. As part of the development of the Federal project â€œExport of agricultural productsâ€, it is necessary to assess at the regional level the capabilities of the Russian regions in terms of developing the export component and ensuring the implementation of the relevant indicators. In order to achieve these goals, we need a rational mechanism for allocating budget funds to support those regions that have prospects for increasing the production of export-oriented products, but for objective reasons, this mechanism is not available yet. The absence of an organizational and economic mechanism for state support of agricultural exports is not an incentive for further development of production and processing of agricultural products. This also does not contribute to the growth of Russiaâ€™s export potential. In our opinion, it is advisable to determine the possible components of such a mechanism, taking into account the characteristics of each region, for further generalization and optimization. Taking into account the export potential of the region and the prospects for its improvement, it will be effective to use various tools: the development of long-term comprehensive programs for the development of export-oriented industries, stimulating regional taxpayers-exporters, and providing subsidies for the development of the export logistics system.